PENGARUH KEPUASAN KERJA TERHADAP KOMITMEN ORGANISASI - Marnoto Marnoto; Santo Dewatmoko (PUBLISHER ABISATYA DINAMIKA ISWARA PUBLISHING, 2022)
ABSTRACT Lecturers are one of the pillars that determine the success of educational activities at universities. The existence of lecturers must always be given serious attention, considering that the success of the learning process is very difficult to achieve if the role of the lecturer is marginalized. Components that support the success of the learning process, lecturer performance must be maintained and improved. This study aims to analyze the effect of job satisfaction on organizational commitment at the Ariyanti Academy of Secretary and Management. The method used in this research is a survey approach and the nature of this research is explanatory research (explanation). The number of samples in this study was 61 lecturers, using the total sampling technique (population = sample). The data analysis method used is path analysis using SPSS software. The results showed that job satisfaction has a positive and significant effect on organizational commitment. Keywords: Job Satisfaction, Commitment, and Organization